275. PREOPERATIVE 3D-CT EVALUATION OF THE BRONCHIAL ARTERIES IN TRANSMEDIASTINAL RADICAL ESOPHAGECTOMY FOR ESOPHAGEAL CANCER. (24th September 2022) - Maeda, Tomohito; Fujiwara, Hitoshi; Konishi, Hirotaka; Shiozaki, Atsushi; Nishibeppu, Keiji; Ohashi, Takuma; Kubota, Takeshi; Kiuchi, Jun; Arita, Tomohiro; Shimizu, Hiroki; Yamamoto, Yusuke; Morimura, Ryo; et al.
Abstract: Transmediastinal radical esophagectomy (TME) is the esophagectomy without thoracotomy that can achieve the mediastinal lymphadenectomy equivalent to transthoracic procedure. Understanding of surgical anatomy in the deep mediastinum near the aortic arch or tracheal bifurcation is essential for the safe procedure. The present study aims to evaluate the bronchial arteries (BAs) with preoperative 3D-CT for TME. Seventy-nine patients with thoracic esophageal cancer undergoing TME were examined by preoperative 3D-CT to evaluate BA variations in the number, branching pattern, and mediastinal course. For the right BAs (RBAs) crossing the esophagus, the mediastinal courses in transcervical view were classified in relation to the esophagus and tracheobronchi, and compared with surgical findings. A total of 107 RBAs (1.35/person) were confirmed on preoperative 3D-CT. Of these, 61 (57.0%) crossed the esophagus dorsally (type Ed), and the remaining 46 (43.0%) crossed the esophagus ventrally (type Ev). During the left transcervical procedure, all type Ed RBAs were identified and mostly preserved (57/61, 93.4%) whereas most type Ev RBAs were identified (39/46, 84.8%), but more than half were sacrificed (26/46, 56.5%) for lymphadenectomy. The blood loss during the transcervical procedure was 17.0 ± 55.8 mL. The total number of dissected mediastinal lymph nodes was 23.7 ± 9.3. There were no significant complications related to extensive lymphadenectomy. Preoperative 3D-CT evaluation is useful to understand the mediastinal courses of BAs specific to the transcervical approach, which may allow BAs to be handled more carefully according to the type during surgery, contributing to a safer procedure in the deep mediastinum.